2012
DOI: 10.1002/lary.23502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antimicrobial photodynamic therapy on human ciliated respiratory mucosa

Abstract: Background Chronic recurrent sinusitis (CRS) is one of the most common chronic conditions in the United States. There is a significant subpopulation of CRS patients who remain resistant to cure despite rigorous treatment regimens including surgery, allergy therapy and prolonged antibiotic therapy. Antimicrobial photodynamic therapy (aPDT) is a non-invasive non-antibiotic broad spectrum antimicrobial treatment. Our previous in vitro studies demonstrated that aPDT reduced CRS polymicrobial biofilm and planktonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…[344][345][346][347] Photodynamic therapy is a new and promising treatment that shows tremendous biofilm reductions in vitro, and preliminary tissue studies have not shown deleterious side effects. 348,349 Last, low-frequency ultrasound treatments also seem effective in reducing biofilms, also without observed side effects. 350 A promising new approach to understanding biofilms involves bitter taste receptors in the upper respiratory tract.…”
Section: S55mentioning
confidence: 99%
“…[344][345][346][347] Photodynamic therapy is a new and promising treatment that shows tremendous biofilm reductions in vitro, and preliminary tissue studies have not shown deleterious side effects. 348,349 Last, low-frequency ultrasound treatments also seem effective in reducing biofilms, also without observed side effects. 350 A promising new approach to understanding biofilms involves bitter taste receptors in the upper respiratory tract.…”
Section: S55mentioning
confidence: 99%
“…In an in-vitro model, Biel et al [33,34 && ] demonstrated that photodynamic therapy diminished MRSA and antibiotic-resistant Pseudomonas aeruginosa biofilms by over 99% after a single treatment. In addition, it has been shown that photodisinfection does not affect normal human-ciliated respiratory mucosa at a histological level, and that no 'photoresistance' occurs with repetitive treatment [35]. Clinical trials investigating the efficacy of photodisinfection in the treatment of CRS are currently being conducted [36].…”
Section: Sinonasal Photodynamic Therapymentioning
confidence: 99%
“…aDPT has also demonstrated efficacy in preventing surgical site infections when used in pre-operative decolonization therapy in conjunction with chlorhexidine body wipes, in the treatment of chronic periodontitis, and in reducing biofilm formation on orthopedic prosthetic devices [8183]. aPDT does not cause histologic damage to the underlying respiratory mucosa and appears to be a promising and viable option for biofilm eradication, especially in antibiotic resistant cases [84]. …”
Section: Emerging Treatmentsmentioning
confidence: 99%